Melaka state climate action plan 2020 - 2030 - Zen, Irina Safitri; Hashim, Haslenda; Sinniah, Gobi Krishna; , (Melaka Green Technology Corporation, 2019)
Executive Summary  The Melaka State Climate Action Plan (MSCAP) 2020 – 2030 is a state- and communitywide action plan which was based on the Greenhouse Gas (GHG) inventory data as of year 2015. It was co-developed by the team of expert from Universiti Teknologi Malaysia, the officers in Melaka GreenTech and the stakeholders in Melaka state which can be a basis for Melaka Climate Governance.  Six main sectors were identified from the Melaka Climate Resolution 2019, Melaka Climate Action Plan Stakeholder Workshop. The six are Public & Stakeholder Engagement, Climate Governance, Energy, Transport, Waste, Ecosystem & Biodiversity.  The development of detail GHG emission sources helps agencies to determine the major sources of carbon emissions, identify the strategies for mitigation and adaptation in order to reduce these emissions and improve the overall resilience of the city.  MSCAP was developed as a guide for structured and continuous action to translate the Melaka State GHG Inventory Report. It was developed to strategize the Melaka contribution towards the Nation voluntary commitment on CO2 reduction by identifying emissions from various sectors and activities in Melaka.  Community- and sector-wise GHG inventory reveals the characters of carbon emitters and helps in assigning the responsibility for further climate mitigation and adaptation action.  As of year 2030, Malaysia national target for carbon emission reduction is 45% and the Melaka State GHG emissions reductions target set up for 45 % or equivalent to 5,703 MT CO2e.  Per capita GHG emission for Melaka State was recorded 5.09 tCO2e in 2015 based on 872,900 population.  In line with the trends of energy demand, the major contributors to GHG emissions are industrial energy use with 1,590 MT CO2e (35.77 %), on-road transportation with 1,115 MT CO2e (25.09 %) and commercial / institutional buildings and facilities with 733 MT CO2e (16.49 %).  Climate resolution for Melaka State (2020 – 2030) is a result of the Melaka Climate Stakeholder LONG TERM 45% reduction or 5,703 MT CO2e by Year 2030 MEDIUM TERM 30% reduction or 2,663 MT CO2e by Year 2025 SORT TERM 20% reduction or 1,252 MT CO2e by Year 2030